PENGARUH TRANSPARANSI, AKUNTABILITAS, PARTISIPASI, DAN KOMPETENSI APARATUR TERHADAP KINERJA PENGELOLAAN ALOKASI DANA DESA DAN DANA DESA DENGAN MODERASI SISTEM PENGENDALIAN INTERNAL PADA DESA DI KECAMATAN SANO NGGOANG KABUPATEN MANGGARAI BARAT - Maria Kornelia Suryani; Muhammad Taufiq Hidayat (Gapenas Publisher, 2023)
This study aims to determine and examine the effect of transparency, accountability, participation, and competence of apparatus on the performance of managing village fund allocations and village funds by moderating the internal control system in villages in the Sano Nggoang sub-district, Manggarai Barat Regency. The research method that was used in this researchis a quantitative approach. The population in this study were 5 villages in Sano Nggoang District with a purposive sampling technique with a sample size of 45 respondents. Source of data in this study is primary data and data collection techniques using a questionnaire with a Likert scale. The data analysis technique uses multiple linear regression analysis and Moderated Regression Analysis (MRA) with an analytical approach. The results of the multiple linear regression analysis show that transparency and accountability have a significant effect on the management performance of village fund allocations and village funds, while apparatus participation and competence have no significant effect on the management performance of village fund allocations and village funds. Moderation regression analysis shows that the internal control system can moderate the transparency of the management performance of village fund allocations and village funds, while the internal control system cannot moderate the accountability, participation and competence of apparatus on the management performance of village fund allocations and village funds